Problems of teaching foreign languages at Russian universities in the conditions of the COVID-19 pandemic - Petrova Lyudmila Nikolaevna (SHS Web of Conferences, 2021)
The relevance of the research is accounted for by the contradiction between the mass-scale transition of the Russian universities to the distance learning format and the insufficient readiness of the educational process participants in the conditions of COVID-19 pandemic. The following methods of theoretical (analysis, synthesis, systematisation, comparison) and empirical (review of literature, interviewing, questioning, observation) research were comprehensively used in the paper. The situation with distance education before the pandemic was analysed; the prerequisites of the problems and difficulties of transition to online education were identified. The analysis of difficulties encountered by the teachers and students of Russian universities made it possible to identify the objective and subjective factors of their emergence, as well as to develop recommendations for further continuation of distance learning in its combination with the traditional format of education. The purpose of the research was the analysis of the current experience of working in the conditions of COVID-19 pandemic by the example of teaching the disciplines “Foreign language” and “Foreign language (legal aspect)” to the students of Plekhanov Russian University of Economics. The authors analysed the reasons of success and problems, showed the contradictions between the remote and traditional forms of learning. The key models of learning organisation involving traditional and distant forms of education with the use of remote education technologies were reviewed. In addition, an analysis of works by a number of Russian and foreign researchers on the problem of distance learning was undertaken. As a result of the research, a conclusion was made that distance learning in the modern system of higher education in Russia may be considered as a complementary form of the already existing traditional (“face-to-face”) learning format, enhancing it, and this synthesis of forms may be considered as a solution of the emerging problems in the course of learning in the pandemic environment.